2018
DOI: 10.1021/acs.joc.8b02602
|View full text |Cite
|
Sign up to set email alerts
|

Studies toward the Total Synthesis of Nogalamycin: Construction of the Complete ABCDEF-Ring System via a Convergent Hauser Annulation

Abstract: The convergent synthesis of the complete ABCDEF-ring system within nogalamycin, an anthracycline natural product, was studied. The pivotal Hauser annulation for the anthraquinone core construction was achieved by the fusion of two highly functionalized segments: a cyanophthalide (the AB-ring segment) and a tricyclic quinone monoketal (the DEF-ring segment). Key transformations toward the AB-ring segment include an enantioselective enolate α-hydroxylation, a diastereoselective hydroborationoxidation, and a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, while there is no reported total synthesis of NOG, there are approaches to the simpler analogue MEN. ,, Terashima et al used a Diels–Alder cycloaddition between a CDEF-ring quinone fragment and AB-ring diene to furnish MEN with 28 steps in the longest linear sequence. , Hauser et al employed a key Hauser annulation to give racemic MEN with a longest linear sequence of 30 steps and published an enantioselective synthesis of the DEF-ring system in 2000 . Related model studies toward the preparation of the CDEF fragment include work by the groups of Krohn et al and Franck et al, while strategies to forge the anthracycline core were reported by Wulff et al , The VanNieuwenhze group achieved the most advanced partial synthesis of NOG using a late-stage convergent synthesis involving a key Hauser annulation. Despite this success, approaches to the shared CDEF-ring of MEN and NOG are lengthy and scaffold diversification must be done early in the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, while there is no reported total synthesis of NOG, there are approaches to the simpler analogue MEN. ,, Terashima et al used a Diels–Alder cycloaddition between a CDEF-ring quinone fragment and AB-ring diene to furnish MEN with 28 steps in the longest linear sequence. , Hauser et al employed a key Hauser annulation to give racemic MEN with a longest linear sequence of 30 steps and published an enantioselective synthesis of the DEF-ring system in 2000 . Related model studies toward the preparation of the CDEF fragment include work by the groups of Krohn et al and Franck et al, while strategies to forge the anthracycline core were reported by Wulff et al , The VanNieuwenhze group achieved the most advanced partial synthesis of NOG using a late-stage convergent synthesis involving a key Hauser annulation. Despite this success, approaches to the shared CDEF-ring of MEN and NOG are lengthy and scaffold diversification must be done early in the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Some of the other common features shared by these structures include the presence of an angular methyl group at the ring junction and the fact that they still remain elusive to total synthesis. 14 Our synthetic strategy to access the DEF-benzoxocin tricyclic core of nogalamycin hinges on the sequential functionalization of hydroquinone 1,5-bis-glycopyranoside derivatives I bearing simultaneously a quaternary and a tertiary anomeric center (Scheme 2). Previous work in our group has shown that such key intermediates bearing the characteristic angular methyl group of nogalamycin anthracyclines and related compounds could be obtained from exo-glycals and 1,4-quinones by way of metal hydride HAT.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This natural anthracycline isolated from Streptomyces nogalator possesses biological activity versus Gram-positive bacteria and prominent cytotoxicity against L1210 and KB cell lines in vitro (Scheme 2). 13,14 Menogaril, a simplified semisynthetic derivative, was found to display stronger anticancer activity and less toxicity than nogalamycin. However, its development for clinical use was stopped due to undesirable side effects in non-Hodgkin's lymphoma patients.…”
Section: ■ Introductionmentioning
confidence: 99%